Performance and mortality of farmed hares. (20th February 2015) - Rigo, N.; Trocino, A.; Poppi, L.; Giacomelli, M.; Grilli, G.; Piccirillo, A.
Abstract : Performance and mortality of hares were evaluated for 2 consecutive years in a large farm in Veneto Region (Northern Italy). On average, fertile reproductive pairs ( n =318) gave birth 4.8 times and produced 11.4 live leverets, weaned 8.4 leverets and produced 7.0 growing hares (60 days) every year. Mean mortality was 3.6%, 22.9%, 9.7% and 2.5% in newborn (0 to 2 days of age), suckling (3 to 25 days), growing (26 to 60 days) and sub-adult (61 days until sale) hares, respectively. The main causes of mortality were enteric diseases (75.5%, 75.9% and 12.1% in suckling, growing and sub-adult hares, respectively), followed by respiratory diseases (3.4%, 8.0% and 36.2% in suckling, growing and sub-adult hares, respectively), starvation (11.3% and 8.8% in suckling and growing hares, respectively) and trauma (7.1%, 2.3% and 30.2% in suckling, growing and sub-adult hares, respectively). In reproducing hares, mortality was 24.7% and 15.4% in 2010 and 2011, respectively. Respiratory diseases (34.8%) and ulcerative pododermatitis (18.9%) were the most common pathological changes detected in reproducing hares. Farmed hares seem to be affected by diseases resembling those of rabbits reared under intensive conditions. It seems necessary to improve the husbandry of hares to reach satisfactory technical standards and to preserve their health.